Polyethylene terephthalate as a partial replacement for the fine aggregate in concrete mixes (2019)
This research paper, financed by the Eafit University, presents the experimental results in which resistance to compression and manageability of a concrete mix made with a partial replacement for the fine aggregate with polyethylene terephthalate (PET) was assessed. The replacement was made by volume, thus the space occupied by the extracted sand particles will be occupied by the PET. Different concrete mixes with sand replacement were made going from 0 % (reference), 5 %, 10 %, 15 % and 20 %. The results indicate that increasing the replaced sand percentage decreases the resistance to compression, nonetheless, the manageability is not affected by keeping the granulometric curvature of the aggregates. The replacement percentage of 15 % was determined as the more adequate given its appropriate manageability, a great amount of sand is replaced and an acceptable resistance to compression is obtained.